Question of Genre: An Approach to Recognitions of Clement as a Work of Romance - Öztürk, Fatih; Tuğan, Abdullah Gökhan (My University, 2024)
One of the earliest Christian texts, Recognitions of Clement has a highly important place within the Western literature. A work with many questions as to its certain date and author, it is often accepted to be written in the third or fourth century by one Clement, most probably Pope Clement I. In terms of genre, too, the work has aroused some suspicions. Although it is generally taken as a novel, it comprises enough elements to be handled as a piece of romance. As one of the basic components of romance, physical and spiritual quest is a core issue in Recognitions. Furthermore, the concept of love, as an element of romance, has a central role in the story. This article aims to bring a new approach to Recognitions of Clement as a work of romance. By displaying its similarities to one of the romances of the time, Apollonius of Tyre, it is meant to prove Recognitions as a romance through the concepts of quest and love.
Keywords: Romance; love; quest; Recognitions of Clement; Apollonius of Tyre